History of industry and trade of the Philippines. - Hartendorp, A. V. H.,1893- (Manila : American chamber of Commerce of the Philippines, 1958)
A revision and expansion of the author's previously of the published "Short history of industry and trade of the Philippines"
Keywords: Philippine -- History; Philippine -- Commerce; Philippines -- History -- Republic -- 1946